Security-constrained power generation scheduling with thermal generating units, variable energy resources, and electric vehicle storage for V2G deployment. (December 2015) - Haddadian, G.; Khalili, N.; Khodayar, M.; Shahiedehpour, M.
Highlights: The assimilation of electric vehicles, renewable energy sources, and smart grid is introduced. The impact on power system security, emission reduction, and economic operation is introduced. Storage is used in power systems for peak load shaving and minimizing wind curtailment. Abstract: This paper investigates the role of integration of distributed storage with high penetration of variable renewable sources in power systems. The paper analyzes the impact of such integrations on the security, emission reduction, and the economic operation of electric power systems. The paper also identifies strategies for a larger penetration of variable generation resources without compromising the power system security. Mixed integer linear programing (MILP) is applied for the optimization of the day-ahead hourly security-constrained unit commitment. The assimilation of EVs (both as a provider and a utilizer of energy), renewable energy sources, and smart grid is regarded as a novel, low-cost, and low-emission solution to the existing challenges of electric power systems including the means of storing large quantities of energy considering variable renewable energy sources and large carbon footprints of conventional thermal units. Numerical studies are conducted in this paper to showcase the potential impacts of EV fleets as battery storage for peak load shaving, minimizing power grid operation costs and hourly wind curtailments, and optimizing the environmental impacts based on hourly commitment and dispatch of thermal generating units.